Bayern in der NS-Zeit : (Oldenbourg)
4: Herrschaft und Gesellschaft im Konflikt, Teil C / hrsg. von Martin Borszat, Elke Fröhlich, Anton Grossmann. - 1981. XXIV, 730 p. : ill. - Index. - ISBN 3-486-42391-6